Ecotheology: The Christianity's Responsibility to the Environment: Ekoteologi: Tanggung Jawab Kekristenan terhadap Lingkungan Hidup - Sabda Budiman; Enggar Objantoro (GRAFTA: Journal of Christian Religion Education and Biblical Studies, 2022)
Environmental issues have become an important topic to discuss in the 21st century.  The earth is in crisis. Following up on the reality of the environmental crisis, there needs to be an attitude from humans to preserve the environment. The maintenance of the environment is also inseparable from the participation of Christians. This scientific work aims to lay out the Biblical basis of Christian ecoteology and the role of Christianity in maintaining the environment. This research uses qualitative-descriptive research methods. The results and discussions in this scientific work are clear that both the Old and New Testaments clearly order that man preserve the environment. The important aspects that the author finds in maintaining the environment are awareness in understanding, awareness in utilization, and awareness in maintenance.